Guidelines for basic life support. European Resuscitation Council Basic Life Support Working Group. (1993)
A basic life support working group of the European Resuscitation Council was set up in 1991. It was given the objective of producing agreed standards of basic life support to ensure uniform teaching of the techniques to health care professionals and lay people throughout Europe. A common complaint in the past, particularly from members of the public who have received instruction in basic life support, is that different organisations teach different techniques. This problem exists within countries as well as among countries. The European Resuscitation Council presents below its basic life support guidelines, which it hopes will be detailed enough to avoid any ambiguities and to be acceptable for use in all the countries represented by the council.